Effect of Cassava Flour Characteristics on Properties of Cassava-Wheat-Maize Composite Bread Types - Maria Eduardo; Ulf Svanberg; Jorge Oliveira; Lilia Ahrné (International Journal of Food Science)
Replacement of wheat flour by other kinds of flour in bread making is economically important in South East Africa as wheat is mainly an imported commodity. Cassava is widely available in the region, but bread quality is impaired when large amounts of cassava are used in the bread formulation. Effect of differently processed cassavas (sun-dried, roasted and fermented) on composite cassava-wheat-maize bread quality containing cassava levels from 20 to 40% (w/w) was evaluated in combination with high-methylated pectin (HM-pectin) added at levels of 1 to 3% (w/w) according to a full factorial design. Addition of pectin to cassava flour made it possible to bake bread with acceptable bread quality even at concentration as high as 40%. In addition to cassava concentration, the type of cassava flour had the biggest effect on bread quality. With high level of cassava, bread with roasted cassava had a higher volume compared with sun-dried and fermented. The pectin level had a significant effect on improving the volume in high level roasted cassava bread. Crumb firmness similar to wheat bread could be obtained with sun-dried and roasted cassava flours. Roasted cassava bread was the only bread with crust colour similar to wheat bread.